Training and development as a tool for improving basic service delivery; the case of a selected municipality - Mpofu, Mthokozisi (2015)
Municipal employees have come under fire for poor performance and conduct in their work as some engage in corruption and others are not qualified enough to discharge their duties to the required levels. Employee training and development has become one of the key aspects in improving employee performance in organisations, thus leading to improved organizational performance and growth. The study investigated the relationship between the quality of employee training and development on service delivery in a selected municipality with data collected from 150 employees. The results indicated the need for effective employee training and development systems and processes to achieve improved employee performance thus improved provision of basic services to the communities. Doi: http://dx.doi.org/10.1016/j.jefas.2015.10.004